DAMPAK CYBERBULLYING DI MEDIA SOSIAL PADA REMAJA DAN IMPLIKASINYA TERHADAP PELAYANAN BIMBINGAN DAN KONSELING - Triyono Triyono; Rimadani Rimadani (Jurnal Neo Konseling, 2019)
This research is motivated by the existence of teenagers who experience various impacts of cyberbullying in social media. The purpose of this study was to describe 1) The physical impact of cyberbullying on social media in adolescents x 2) The psychological and emotional impact of cyberbullying in social media 3) The emotional psychosocial impact of cyberbullying on social media. This research is a qualitative research that is case study. The research was conducted by observation and interview method with key X informant and 3 additional informants consisting. The results revealed that 1) The physical impact of cyberbullying in adolescents X is feel headache, no appetite, feel sleep disorders, and tired. 2) The psychological and emotional impact of cyberbullying in adolescents X is feelings of sadness, fear and anger. 3) The psychosocial impact of cyberbullying in adolescents X is feeling of isolation, loneliness, and exclusion. Based on the results of the study, it is recommended for adolescents, parents and also to counselors to be able to provide information services, group guidance and individual counseling with assertive training techniques to teenagers.